Gestão do Capital Humano como Fomento ao Processo de Inovação: o caso de uma cooperativa agroindustrial - Catczu, Thatiany Simone (2017)
This study was developed from the perspective of the Resource-Based View theory - RBV, which deals with the capabilities and resources of the company that generate competitive advantage. These resources can be defined as tangible and intangible assets, being that human capital is considered one of the most valuable resources of organizations. That is why it is important to perform human capital management efficiently, it will bring significant results to the organization with a focus on innovations that can improve or even create new products, services and processes. The organizations need to develop continuously their capacity for innovation, since the companies do not compete for new products, but for the capacity to develop them, bringing products and services with more quality to the market, and improving internal processes. In this way, the companies with high innovation performances will be better prepared to work in constantly changing environments. Thus, the dynamic capacity of the company has a strong relation with its capacity for innovation. So, this study had as main purpose to understand if the innovation process is being influenced by the practices related to human capital management in an Agro-industrial Cooperative, within the context of dynamic capabilities. It was used the qualitative approach as methodology by the descriptive case study of transversal nature. As data collection instruments, semi-structured interviews were conducted with ten employees of the Cooperative, among these, there were managers, coordinator and employees in the operational and administrative areas. It also counted with the participant observation and the documents and files survey of the company in the data collection. For the data analysis, it was used the content analysis in the thematic modality and the triangulation technique. The main results showed that there are several tools and programs that enable the generation of innovation, among them the CCQ and Six Sigma, which in a period of 5 years that they have been implemented; they bring approximately 400 improvements in several areas of the Cooperative. On the one hand, the results showed that the numbers of innovations could be higher if human capital management focused more on stimulating innovations in the organizational context. It occurs because the innovations, in many cases, do not occur by their own initiative, but because of the demands of the market and the customers. It also verified that the number of improvement projects are increasing gradually, perhaps not in the manner expected. However, it is understood that this is the way to become a more innovative company. It was also observed that the gap between innovate and the capacity needs of the Cooperative to innovate is restricted by the management, policies and the guidelines for innovation. On the other hand, in the approach of the dynamic capacities present in the innovation management in the Cooperative, it was noticed that the company has a great knowledge of its market and, mainly, what are the factors that can influence the changes in its diverse areas of business. That is why it is prepared for environmental contingencies and the dynamism of the market.